2018
DOI: 10.5194/acp-2018-773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polyols and glucose particulate species as tracers of primary biogenic organic aerosols at 28 french sites

Abstract: <p><strong>Abstract.</strong> A growing number of studies are using specific primary sugar species, such as sugar alcohols or primary saccharides, as marker compounds to characterize and apportion primary biogenic organic aerosols (PBOA) in the atmosphere. To better understand their annual cycles, as well as their spatio-temporal abundance in terms of concentrations and sources, we conducted a large study focusing on three major atmospheric primary sugar compounds (i.e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…A large database on concentrations of PM 10 SC at study sites has been acquired previously at many sites all over France ( Samaké et al, 2019a , b ), including the three sites of this study. It has already been shown that arabitol, mannitol, glucose, and trehalose are generally the main SC species in all urban and rural areas investigated in France ( Samaké et al, 2019a ). Their mean annual and summer concentrations at the 3 sites of the present study for the years 2017 and 2018 are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A large database on concentrations of PM 10 SC at study sites has been acquired previously at many sites all over France ( Samaké et al, 2019a , b ), including the three sites of this study. It has already been shown that arabitol, mannitol, glucose, and trehalose are generally the main SC species in all urban and rural areas investigated in France ( Samaké et al, 2019a ). Their mean annual and summer concentrations at the 3 sites of the present study for the years 2017 and 2018 are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Details on the chemical analysis of aerosol are presented elsewhere ( Golly et al, 2018 ; Samaké et al, 2019a , b ). Briefly, each aerosol sample was analyzed for various chemical species using subsampled fractions of the collection filters and a wide range of analytical methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, for primary sources, levoglucosan is commonly used to trace biomass burning emissions, polyols for biogenic emissions (fungal spores), hopanes for vehicular emissions, etc. (Cass, 1998;Samaké et al, 2019aSamaké et al, , 2019bSchauer et al, 1996;Simoneit et al, 1999).…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…Furthermore, anhydro-sugars and saccharides were analysed by a High Performance Liquid Chromatography with Pulsed Amperometric Detection (HPLC-PAD), using a Thermo-Fisher ICS 5000 + HPLC equipped with 4 mm diameter Metrosep Carb 2×150 mm column and 50 mm pre-column in isocratic mode with 15% of an eluent of sodium hydroxide (200 mM) and sodium acetate (4 mM) and 85% water, at 1 ml min -1 . This method notably allowed the quantification of anhydrous saccharides (levoglucosan and mannosan), polyols (arabitol and mannitol), and glucose as tracers of biomass burning and primary biogenic aerosols (Samake et al, 2018;Waked et al, 2014).…”
Section: Classical Set Of Chemical Analysesmentioning
confidence: 99%